2021
DOI: 10.1002/nau.24567
|View full text |Cite
|
Sign up to set email alerts
|

Losartan prevents bladder fibrosis and protects renal function in rat with neurogenic paralysis bladder

Abstract: Aims: To investigate the effect of losartan on preventing bladder fibrosis and protecting renal function in rats with neurogenic paralysis bladder (NPB). Materials and Methods: Rats were assigned to the transecting spinal nerves group (TSNG), transecting spinal nerves + losartan group (LSTG), and control group (CG). On Day 32 postsurgery, bladder capacity (BC), bladder compliance (ΔC), bladder leakage pressure (P ves.leak) of TSNG and LSTG while BC, ΔC, and bladder threshold pressure (P ves.thre) of CG were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This is consistent with the previous findings by others. For example, losartan alleviates renal fibrosis in rats with nephrectomy by down-regulating HIF-1alpha and up-regulating MMP-1/TIMP-1 or through inhibition of ER stress via up-regulation of SIRP1, followed by induction of HO-1 and thioredoxin ( He et al, 2014 ; Kim et al, 2017 ); it attenuates renal interstitial fibrosis and tubular cell apoptosis in a rat model of obstructive nephropathy ( Song et al, 2019 ) and accelerates the repair process of renal fibrosis in UUO mouse after the surgical recanalization by upregulating the Tregs expression ( He et al, 2021 ). Most recently, losartan is shown to prevent bladder fibrosis and protects renal function in rat with neurogenic paralysis bladder ( Norris et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the previous findings by others. For example, losartan alleviates renal fibrosis in rats with nephrectomy by down-regulating HIF-1alpha and up-regulating MMP-1/TIMP-1 or through inhibition of ER stress via up-regulation of SIRP1, followed by induction of HO-1 and thioredoxin ( He et al, 2014 ; Kim et al, 2017 ); it attenuates renal interstitial fibrosis and tubular cell apoptosis in a rat model of obstructive nephropathy ( Song et al, 2019 ) and accelerates the repair process of renal fibrosis in UUO mouse after the surgical recanalization by upregulating the Tregs expression ( He et al, 2021 ). Most recently, losartan is shown to prevent bladder fibrosis and protects renal function in rat with neurogenic paralysis bladder ( Norris et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although He et al. [ 24 ] found a protective effect with four weeks of ‘losartan’ treatment on bladder fibrosis and renal function, a long-term study of treatment observation after NBF is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The anterior and posterior diameters of the renal pelvis were measured using a multifunctional Doppler ultrasound (LOGIQ E9; GE, Boston, MA, USA) and a 4–15 MHz probe to evaluate hydronephrosis. Rats were anaesthetized by intraperitoneal injection of urethane [ 23 ] at a concentration of 20% and a dose of 1 g/kg, and a blunt epidural catheter with a diameter of 1 mm was smeared with a paraffin oil globule and inserted into the bladder for cytometry, as described in our previous publication [ 24 ]. Bladder pressure curves and basal bladder pressure, P ves.thre (bladder pressure just before voiding), P ves.leak (pressure in the bladder when filling incontinence occurs), P ves.max (maximum pressure during voiding), voiding interval, and time to first leakage were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…It is generally believed that bladder wall fibrosis plays an important role in NB ( 26 ). In the present study, the Masson and H&E staining results showed thickening of the bladder wall, disordered and hypertrophic detrusor cells, and proliferative collagen fibers in NB model rats.…”
Section: Discussionmentioning
confidence: 99%